Patient Attitudes to Intensive Care and Life-Sustaining Technology. (October 2014) - Tully, Redmond P; Kitchen, Gareth; Tufchi, Aseem; Saha, Bhaskar; Baker, Rose
We used a validated questionnaire to explore the views of patients regarding receiving intensive care and life-sustaining technology. Data was obtained from 38 patients. A score was obtained for 'general attitude towards use of life-sustaining/prolonging technology' that varied from 18.9 to 48.5 out of 52, the higher score reflecting a more positive attitude. There was no significant difference between men and women or correlation with age or ASA score. A score for 'personal desire for life support' was also obtained, ranging from zero to a maximum possible score of eight, which reflected the most positive view. The median score was 0.5. Women had a significantly lower median score of zero vs 1.5 for men (p=0.022). There was no significant correlation with age or ASA score. There was considerable heterogeneity of views regarding the use of life-sustaining technology. In this study, women were less likely to want intensive medical treatment than men.